Use of Probiotics in Treating Pediatric Gastrointestinal Disorders (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In this article is discussed the current understanding and application of probiotics in modern medicine, with an emphasis on pediatric gastroenterology. It highlights the therapeutic potential of probiotics—live microorganisms that support gut health—by restoring the balance between harmful and beneficial intestinal flora, especially during and after antibiotic treatment. Probiotics play a vital role in preventing and managing conditions such as antibiotic-associated diarrhea, acute intestinal infections, and other gastrointestinal and immune-related disorders in children.